Globalization of Freshwater Resources: Innovative Management Strategy - Marina Boykova; Diana Krupnikova (Foresight and STI Governance, 2010)
The population of the world has grown substantially during the last half a century, and the demand for water amounted to one third of contemporary volume.The paper investigates the issue of water shortage which increases more rapidly than it was predicted; its transportation is considered to be even more complicated than that of oil.The latest findings enable experts to make an optimistic assessment — the total amount of freshwater recourses is enough for life sustaining on the planet. However, as the authors suggest, the matter is not just the quantity or quality of water resources, but their adequate management.The authors point out that vast intellectual capital has been accumulated by now, and it enables to set up an integrated system of freshwater resources management in order to prevent dramatic scenarios.